Cirkulišući lncRNA DRAIC kao potencijalni biomarker seruma za predviđanje limfnog i vaskularnog širenja kod raka pankreasa: Serum DRAIC kao biomarker u računaru - Che, Ying; Zhang, Ting; Li, Jing; Jiang, Xiao; Li, Chao; Li, Wei (Journal of Medical Biochemistry, 2026)
Background: Pancreatic cancer is notorious for its aggressive behavior and poor prognosis, largely due to delayed diagnosis and early dissemination. Identifying reliable serum biomarkers could enhance early detection and risk stratification. Long non-coding RNAs (lncRNAs) have been recognized as regulators of tumor biology, however, the clinical and biochemical relevance of lncRNA DRAIC in pancreatic cancer has not been fully elucidated.Methods: Serum samples were obtained from 100 patients diagnosed with pathologically confirmed pancreatic cancer and 100 age- and sex-matched controls. Quantitative real-time polymerase chain reaction (qPCR) was employed to quantify the circulating DRAIC expression levels. We analyzed the associations between serum DRAIC levels and clinicopathological characteristics, including vascular involvement and lymph node metastasis. Receiver operating characteristic (ROC) curve analyses were performed to assess the diagnostic and predictive performance of DRAIC. Paired serum samples obtained before and after surgical resection were additionally analyzed.Results: Serum DRAIC expression was significantly elevated in patients with pancreatic cancer compared with controls. ROC analysis demonstrated robust diagnostic potential (AUC = 0.943). Elevated DRAIC levels were significantly associated with lymph node metastasis and vascular involvement. DRAIC showed strong predictive performance for lymph node metastasis (AUC = 0.906), whereas its predictive value for vascular involvement was moderate. Notably, serum DRAIC levels were significantly reduced following surgical resection.Conclusion: Circulating lncRNA DRAIC is markedly dysregulated in pancreatic cancer and demonstrates potential utility as a serum-based biochemical biomarker, particularly for evaluating lymph node metastasis. These findings provide a basis for further mechanistic studies and validation in larger cohorts.